Effect of deformation parameters on microstructure of martensitic stainless steel during static recrystallization. Issue 1 (March 2021) - Ren, Facai; Si, Jun; Xu, Jinsha
Abstract: In this paper, the static recrystallization behavior of X20Cr13 martensitic stainless steel was studied based on the hot compression test. The experimental results show that when the strain of the first pass is less than the critical strain of dynamic recrystallization, the main static softening mechanism is static recrystallization. The effects of prestrain, initial austenite grain size, deformation temperature and strain rate on the microstructure during static recrystallization were analyzed in detail.